TMEM16F regulates spinal microglial function in neuropathic pain states - Batti, Laura; Sundukova, Mayya; Murana, Emanuele; Pimpinella, Sofia; De Castro Reis, Fernanda; Pagani, Francesca; Wang, Hong; Pellegrino, Eloisa; Perlas, Emerald; Di Angelantonio, Silvia; Ragozzino, Davide; Heppenstall, Paul A. (Cell reports, 2016)
Neuropathic pain is a widespread chronic pain state that results from injury to the nervous system. Spinal microglia play a causative role in the pathogenesis of neuropathic pain through secretion of growth factors and cytokines. Here, we investigated the contribution of TMEM16F, a protein that functions as a Ca2+-dependent ion channel and a phospholipid scramblase, to microglial activity during neuropathic pain. We demonstrate that mice with a conditional ablation of TMEM16F in microglia do not develop mechanical hypersensitivity upon nerve injury. In the absence of TMEM16F, microglia display deficits in process motility and phagocytosis. Moreover, loss of GABA immunoreactivity upon injury is spared in TMEM16F conditional knockout mice. Collectively, these data indicate that TMEM16F is an essential component of the microglial response to injury and suggest the importance of microglial phagocytosis in the pathogenesis of neuropathic pain.